Monitoring treatment of acute kidney injury with damage biomarkers. (15th February 2017) - Pianta, T.J.; Succar, L.; Davidson, T.; Buckley, N.A.; Endre, Z.H.
Abstract: Background: Damage biomarkers may identify mechanisms and sites of acute kidney injury (AKI). However, the utility of novel AKI biomarkers differs by context, and their utility for monitoring treatment of AKI is unknown. We hypothesized that selected AKI biomarkers would facilitate monitoring of mechanism-specific treatment. We examined this using a panel of biomarkers to monitor cisplatin-induced AKI treatment with alpha-lipoic acid (α-LA) that has previously been demonstrated to ameliorate cisplatin induced AKI. Methods: AKI was induced in male Sprague Dawley rats using cisplatin (6 mg/kg) in the presence or absence of a single dose of α-LA (100 mg/kg). A panel of 12 urinary kidney damage biomarkers (Cystatin C, NGAL albumin, alpha-1-acid glycoprotein, clusterin, KIM-1, osteopontin, total protein, cytochrome C, epidermal growth factor, interleukin-18 and malondialdehyde was examined as well as histological injury, serum creatinine and cystatin C, and clinical parameters. Results: Cisplatin treatment modified all parameters, except interleukin-18 and malondialdehyde, with each parameter demonstrating a different temporal profile. α-LA treatment attenuated renal tubular injury scores (P < 0.05), decreased peak serum creatinine (p = 0.004) and cystatin C (p = 0.04), and urinary damage biomarkers of proximal tubular injury (Cystatin C, NGAL, albumin, and alpha-1-acid glycoprotein). Other urinary biomarkers were not modified. Neither α-LA alone, nor the cisplatin vehicle (DMSO) modified biomarker profiles. Conclusions: α-LA treatment ameliorated cisplatin-induced AKI. Protection was demonstrated by reduced structural damage, improved glomerular filtration and reduced excretion of urinary biomarkers of proximal tubular damage. Effective treatment of AKI can be monitored by site and perhaps by mechanism-specific kidney damage biomarkers.